ATORVASTATIN INDUCED ACUTE PANCREATITIS? - A RARE CASE REPORT: Case Report - JAIDEV KUMAR; ASHOKA; RAKSHITH; UMESH (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Acute pancreatitis is a clinical condition characterized by inflammation of pancreas. The specific time interval to suspect any patient as acute pancreatitis is not clearly defined in any therapeutic guideline and usually symptoms will be lasted for a short period of time. The management of acute pancreatitis always depends on underlying cause. The common medications that can cause acute pancreatitis include angiotensin-converting enzyme inhibitors, azathioprine, and pentamidine. According to the patient case history, abdominal pain was on and off; the patient also received nonsteroidal anti-inflammatory drugs, i.e., tablet aceclofenac 100 mg for abdominal pain, whenever he was experiencing pain and it got subsided only for short period. This case report did not have clear subjective and objective evidence to suspect atorvastatin which was the main culprit of causing acute pancreatitis. The incidence of causing drug-induced acute pancreatitis is very low which was accountable for only 0.1–2%. This case report concludes that all health-care professionals need to have close monitoring of atorvastatin causing acute pancreatitis which is very rarely seen.